Path Through the Ruins: How Photojournalists Modeled the Famine in Gaza? - Eftimov, Yordan (Media and Language, 2025)
The report places the reportage footage of the famine in Palestine in the summer of 2025 in the intertext of the photographic tradition of wars and disasters, raising questions of an ethical and aesthetic nature. Two covers of influential publications – The Economist and Time – are put in focus. The scenes of the suffering Palestinians are examined as a replica of photographic images from post-war Germany.
Keywords: Gaza; starvation; social-documentary photography; photographic truth; cultural appropriation; aestheticizing and objectifying the suffering